2021
DOI: 10.1007/s00414-021-02593-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mediastinal-thoracic volume ratio on postmortem computed tomography

Abstract: Objectives The aim of this study was to measure the mediastinal-thoracic volume ratio (CTR_VOL) on PMCT as a more accurate version of traditional CTR, in order to assess the terminal positional relationship between the heart and lungs in the different causes of death with regard to age, gender, BMI, cardiomegaly, and lung expansion. Materials Two hundred fifty consecutive postmortem cases with pre-autopsy PMCT and full forensic autopsy were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Cardiomegaly may be due to primary or secondary pulmonary hypertension (PH) or other underlying mechanisms. Although PH alone did not predict the clinical outcomes in this study, 73% of the patients had TMOR >30%, which was higher than that reported in normal individuals (mean ± standard deviation, 25% ± 6%) [ 7 ]; therefore, we set TMOR at 40% as a stratified standard in this study. Overall, TMOR is a parameter that integrates a relatively small chest cavity and large heart, both of which could be multifactorial.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Cardiomegaly may be due to primary or secondary pulmonary hypertension (PH) or other underlying mechanisms. Although PH alone did not predict the clinical outcomes in this study, 73% of the patients had TMOR >30%, which was higher than that reported in normal individuals (mean ± standard deviation, 25% ± 6%) [ 7 ]; therefore, we set TMOR at 40% as a stratified standard in this study. Overall, TMOR is a parameter that integrates a relatively small chest cavity and large heart, both of which could be multifactorial.…”
Section: Discussionmentioning
confidence: 59%
“…These volumes were obtained using Synapse Vincent (Fuji Film Co., Ltd., Tokyo, Japan). Semi-auto extraction with a manual operation was used to obtain the volumes of the thoracic cage and mediastinum [ 7 , 8 ]. To ensure the quality of the extraction, all three-dimensional images were assessed by experienced thoracic surgeons (Nobuyuki Yoshiyasu and Masaaki Sato).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Посмертная КТ-ангиография обладает высокой визуализацией для выявления пороков развития сердечно-сосудистой системы у новорожденных [68]. Также возможно применение виртопсии в области антропо-и морфометрических исследований, например, для определения кардиоторакального соотношения [8,19]. Несмотря на то, что данные морфометрии сердца, основанные на аутопсии, могут значительно отличаться от оценки в рамках виртопсии, применение неинвазивных методов может быть дополнено разработкой современных протоколов оценивания изображения и внедрением подходящих морфометрических расчетов.…”
Section: возможности применения виртопсии в практике патологоанатомаunclassified